Spatial and Temporal Variation of Precipitation Drives the Genome Size Variation in Scolopendra in Chinese Mainland - Kai Zhang; Buddhi Dayananda; Yifei Liu; Zhigang Hu; Lin Zhang (Ecology and Evolution)
ABSTRACT Genome size is an adaptive trait, and its variations influence the organismal phenotype and fitness. In this study, we propose a hypothesis linking variations in genome size within Scolopendra to ecological factors. To test this hypothesis, we employed flow cytometry to estimate genome size in seven Scolopendra species from Chinese mainland. Subsequently, we reconstructed the phylogenetic relationship of these species using the cytochrome c oxidase subunit 1 gene and conducted phylogenetic comparative analysis to assess the relationships between genome size and niche breadth or 19 bioclimatic variables. Our findings indicate the following: (1) genome size in Scolopendra can be categorized into three groups, similar to the phylogenetic clades; (2) there is a negative correlation between genome size in Scolopendra species and the precipitation niche breadth of species; (3) the estimated divergence time of Scolopendra dates back 153 Mya, during the Jurassic period. We assume that consistent aridity geological periods may promote the evolution of Scolopendra species with a large genome size, whereas rapidly fluctuating humidity geological periods may have the opposite effect.